Contribution to the knowledge of vascular flora endemism in Veracruz, Mexico - Castillo-Campos, Gonzalo; Medina Abreo, Ma. Elena; Dávila Aranda, Patricia Dolores; Zavala Hurtado, José Alejandro (Instituto de Ecología, A.C., 2005)
A list of the endemic taxa of the vascular flora of the state of Veracruz was obtained. We recorded 131 species and 10 subspecific taxa belonging in 56 families and 94 genera. The families with highest number of endemic species were Orchidaceae (11), Myrtaceae (10), Bromeliaceae (9), Poaceae (8), Begoniaceae (7), Zamiaceae (5) y Polypodiaceae (5). The vegetation types that stand out for concentrating the endemic species are: the evergreen tropical forest (52), the cloud forest (43), the deciduous tropical forest (23), the Quercus forest (20), the coniferous forest (16), the gallery forest (15) and the sub-deciduous tropical forest (11).